“Are you sure it’s not the Corona vaccine?” An Ebola vaccine trial during COVID-19 in DRC - James, M; Lees, S (Taylor and Francis, 2022)
The COVID-19 pandemic began as an Ebola epidemic was unfolding in the Democratic Republic of the Congo. In this article, we examine how COVID-19 influenced experiences of an Ebola vaccine trial and attitudes towards medical research in Goma. First, critical debates about vaccine research became a forum in which to contest ineffective local governance and global inequality. Second, discussions about new COVID-19 therapeutics reignited critique of Western biomedical colonialism. Third, rumors were made powerful through everyday observations of the unexpected adaption of Ebola trial procedures in the pandemic. This illustrates the difficulties of maintaining participants’ trust, when circumstances dictate protocol alterations mid-trial.